Design and Development of A Web-Based Thesis Administration System to Improve the Efficiency of Academic Services - Yoel Cleaver Kalumata; Benny Pinontoan; Mahardika Inra Takaendengan; Wisard Widsli Kalengkongan; Stephano Caesar Wenston Ngangi; Dod Lapihu (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
This research focuses on developing a web-based thesis administration system using the Rapid Application Development (RAD) method to enhance the efficiency of academic services in the Information Systems Study Program. The system is intended to replace manual procedures that are often slow and error-prone, aiming to streamline administrative tasks and improve service quality.The development follows the RAD stages: needs planning, system design, development, and implementation. Data collection methods include literature studies, observations, and questionnaires to ensure the system meets user needs. Research findings show that the system successfully meets the requirements of users within the study program. Testing results demonstrate a notable improvement in administrative efficiency compared to previous manual processes. In conclusion, the RAD-based web system effectively improves academic service delivery by minimizing delays and simplifying administrative processes.